2015
DOI: 10.2196/resprot.4783
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility, Acceptability, and Efficacy of Delivering Internet-Based Self-Help and Guided Self-Help Interventions for Generalized Anxiety Disorder to Indian University Students: Design of a Randomized Controlled Trial

Abstract: BackgroundGeneralized anxiety disorder (GAD) is one of the most common mental disorders among university students; however, many students go untreated due to treatment costs, stigma concerns, and limited access to trained mental health professionals. These barriers are heightened in universities in India, where there are scant mental health care services and severe stigma surrounding help seeking.ObjectiveTo evaluate the feasibility, acceptability, and efficacy of Internet-based, or “online,” cognitive behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Despite the availability of these tools, the scoping literature review suggested there was insufficient evidence on the validity of the apps. The literature review highlighted the need for additional studies on app dissemination and adoption [ 6 , 32 , 44 , 45 , 49 , 53 ] and app validation and treatment integration [ 7 , 43 , 44 , 46 - 48 , 52 , 59 ]. This literature also suggests the potential of integrating such PTSD-related apps with new technologies, such as smartwatches, as an adjunct for improving treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the availability of these tools, the scoping literature review suggested there was insufficient evidence on the validity of the apps. The literature review highlighted the need for additional studies on app dissemination and adoption [ 6 , 32 , 44 , 45 , 49 , 53 ] and app validation and treatment integration [ 7 , 43 , 44 , 46 - 48 , 52 , 59 ]. This literature also suggests the potential of integrating such PTSD-related apps with new technologies, such as smartwatches, as an adjunct for improving treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite potential security issues and obstacles to apps’ dispersion among users, an abundance of calls for more studies on app dissemination and adoption [ 6 , 32 , 44 , 45 , 47 , 49 , 53 ] and on app validation and treatment integration [ 7 , 43 , 44 , 46 - 48 , 52 , 59 ] indicates the importance of developing apps with optimal usability and improve treatment. Of those apps designed to be used in conjunction with clinical treatment, only two currently incorporate specific treatment-related components (PE Coach and CPT Coach).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively very little is known about how internet-based methods of delivery of psychological interventions may be received and used in non-Western cultures by individuals for whom they are designed [ 26 , 27 , 28 ]. A broad scan of literature indicated that although several papers have been published in the last few years on the scope of digital mental health in India, there is a significant dearth of empirical research on internet-based interventions for mental health in the Indian context [ 29 , 30 , 31 , 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, text messaging has been used for reminders, information provision, supportive messages, and self-monitoring, and as an extension of traditional care rather than treatments in themselves (Berrouiguet et al 2016 ). It has been used in India as a means of coaching college students as they used an app to manage anxiety (Kanuri et al 2015 ). More work is needed to establish whether and how text messaging might offer opportunities to manage post-traumatic stress reactions and related problems during and after exposure to PTEs.…”
Section: Technologies For Trauma Survivorsmentioning
confidence: 99%